Presence and Antibiogram of Inhabiting Marine Bacterial Population at the Upper Sub-surface Water of the South East Coast of Bangladesh, Northern Bay of Bengal (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
The present study was conducted to assess the presence of bacterial populations at the upper sub-surface water from the offshore areas near the South East Coast of Bangladesh, the northern Bay of Bengal and to evaluate their antibiotic resistance pattern. Water samples were collected from 5 stations near the South East Coast of Bangladesh, the northern Bay of Bengal. About 38 marine isolates were primarily identified using conventional cultural methods (Mannitol Salt Agar, Chromocult Coliform Agar and Cetrimide Agar). Among them, two gram negative viz. Pantoea spp. and Pseudomonas aeruginosa and one gram positive viz. Micrococcus spp. were identified and confirmed by biochemical and analytical profiling index techniques. The antibiogram results showed that Pantoea spp. and Micrococcus spp. were sensitive to ciprofloxacin, tetracyclin, erythromycin and chloramphenicol, whereas P. aeruginosa was sensitive to ciprofloxacin, azithromycin and streptomycin. However, Pantoea spp. and Micrococcus spp. were resistant to at least 3 antibiotics (oxacillin, cefixime and polymyxin B). But P. aeruginosa was resistant to a number of antibiotics such as oxacillin, cefixime, ampicillin, novobiocin, cephalexin, tetracycline, amoxicillin and kanamycin. Increasing drug resistance potential of microbial organisms gives us signal to go for immediate necessary action on the maintenance of water quality of estuarine and coastal areas.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 9(2), 2020, P 35-44